Role of legal compliance in sustainable supply chains, operations, and marketing - Wood, John D., 1980- (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2014)
This book on sustainable business is for advanced business education students, practicing managers and executives, and environmental lawyers. Sustainability is a global megatrend with ramifications across all functional areas of business. This book addresses an underdeveloped topic in the field of sustainable business, specifically, the use of corporate resources dedicated to legal compliance. Supply chain, operations, and marketing professionals must know what the applicable legal frameworks are in order to comply with the law. In order to promote sustainable business, these same professionals must go beyond mere compliance with these laws. This book assists readers in both respects by (1) offering concise discussions of the primary legal frameworks governing the social, economic, and environmental dimensions of supply chain management, operations management, and marketing; and (2) making the business case for going beyond mere compliance with legal requirements. Each chapter ends with Practical Applications in the form of instructions for practitioners to apply what they have learned in the previous chapter. Written by an expert in environmental law and public policy, this book argues that companies that go beyond mere compliance with social, economic, and environmental safeguards inherent in legal regimes will capture greater benefits and incur fewer risks from their supply chain, operations, and marketing activities. A sustainable company will go beyond mere compliance with the law.
Part I. The role of legal compliance in sustainable business -- 1. Introduction -- 2. Legal compliance is merely a step toward sustainable business -- Part II. Legal compliance in sustainable supply chain management -- 3. SCM social impacts: human trafficking -- 4. SCM environmental impacts -- Part III. Legal compliance in sustainable operations management -- 5. Operations management and water pollution -- 6. Operations management and air pollution -- 7. Operations management and industrial waste -- 8. Operations management and workplace health and safety -- Part IV. Legal compliance and sustainability marketing -- 9. Truth-in-advertising and sustainable product design -- 10. Truth-in-advertising and sustainable product supply chains -- Part V. Legal compliance and climate change mitigation -- 11. EPA's climate change programs to date -- Conclusion -- Notes -- References -- Index.
Part of: 2014 digital library.
Includes bibliographical references (pages 133-141) and index.
Title from PDF title page (viewed on August 4, 2014).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Business enterprises -- Environmental aspects; Sustainable development -- Law and legislation; Environmental law; environmental law; marketing; operations; legal compliance; social license to operate; supply chain management; sustainable business; Electronic books